Exploring the impact of Stein et al.’s levels of cognitive demand in supporting students’ mathematics heuristic problem-solving abilities - Wakhata, Robert; Mutarutinya, Védaste; Balimuttajjo, Sudi (Frontiers in Education, 2023)
This study explored the use of Stein et al.’s levels of cognitive demand (LCD) on evaluation and instructional methods in applying the knowledge of equations and inequalities to learn the topic of linear programming (LP). We investigated students’ specific proficiency levels in solving LP tasks using Stein et al.’s LCD hierarchical framework. A mixed method approach with a quasi-experimental pre-test, post-test, and non-equivalent control group design was adopted. The participants were 175 11th-grade students from Mbale district, eastern Uganda. The results showed that although the urban school's average post-test scores were higher than those of the rural school, students from the rural secondary school improved greatly relative to their peers from the urban school. The post-test scores were better relative to the pre-test (M=56.51±20.88 vs. 42.23±22.49; 𝑝<0.05). Overall, there was a statistically significant difference between students' average grades in pre-test and post-test (Cohen’s d = 0.81>0.5), 95% 𝐶𝐼 [−18.00, −10.56]). Holding other factors constant, it is likely that the significant differences in students’ average grades were entirely due to the application of Stein et al.’s instructional approach. This study, therefore, recommends that educators should apply Stein et al.’s LCD to support the heuristic problem-solving approaches in learning mathematics and LP in particular.